ANALISIS KINERJA PEGAWAI PADA BIRO PEMERINTAHAN DAN OTONOMI DAERAH SEKRETARIAT DAERAH PROVINSI KALIMANTAN TENGAH: ANALYSIS OF EMPLOYEE PERFORMANCE AT THE BUREAU OF GOVERNMENT AND REGIONAL AUTONOMY OF THE REGIONAL SECRETARIAT OF CENTRAL KALIMANTAN PROVINCE - Dian Widhi Pratama; Raden Biroum Bernardianto; Rachmat Hidayat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This research was conducted at the Bureau of Government and Regional Autonomy of the Regional Secretariat of Central Kalimantan Province, it aims to determine the performance of civil servants in the Bureau of Government and Regional Autonomy of the Regional Secretariat of Central Kalimantan Province. The study used primary data taken with 56 (fifty-six) people by census. From the results of the analysis that the researchers conducted can be seen that the Performance of Civil Servants in the Bureau of Government and Regional Autonomy of the Regional Secretariat of Central Kalimantan Province at a good level, this is in all variables of research, namely Knowledge about Work, Quality of Work, Productivity, Adaptation, Initiative and Problem Solving, Cooperation, Responsibility and Ability in Communicating and Interacting. Based on the assessment criteria set, it can be concluded that the Performance Analysis of Civil Servants in the Bureau of Government and Regional Autonomy of the Regional Secretariat of Central Kalimantan Province is relatively good. Things that can be recommended in this study such as organization management that only emphasizes on the approach of procedures, but must be refined through changes in vision and mission, approach, strategy and operational activities in order to create excellent teamwork, working relationships based on participation approaches and work groups (teamwork) in order to achieve the mission of an organization that is efficient, effective and heading in a better direction.